Nurse Practitioner–Physician Comanagement of Patients in Primary Care. (November 2018) - Norful, Allison A.; Ye, Siqin; Van der-Biezen, Mieke; Poghosyan, Lusine
Current demand for primary care services will soon exceed the primary care provider (PCP) workforce capacity. As patient panel sizes increase, it has become difficult for a single PCP to deliver all recommended care. As a result, provider comanagement of the same patient has emerged in practice. Provider comanagement is defined as two or more PCPs sharing care management responsibilities for the same patient. While physician–physician comanagement of patients has been widely investigated, there is little evidence about nurse practitioner (NP)–physician comanagement. Given the large number of NPs that are practicing in primary care, more evidence is warranted about the PCP perspectives of physicians and NPs comanaging patient care. The purpose of this study was to explore NP–physician comanagement in primary care from the perspectives of PCPs. We conducted in-person qualitative interviews of 26 PCPs, including NPs and physicians, that lasted 25 to 45 minutes, were audio recorded, and then professionally transcribed. Transcripts were deidentified and checked for accuracy prior to a deductive and inductive data analysis. Physicians and NPs reported that comanagement increases adherence to recommended care guidelines, improves quality of care, and increases patient access to care. Effective communication, mutual respect and trust, and a shared philosophy of care are essential attributes of NP–physician comanagement. Physicians and NPs are optimistic about comanagement care delivery and find it a promising approach to improve the quality of care and alleviate primary care delivery strain. Efforts to promote effective NP–physician comanagement should be supported in clinical practice.